2014
DOI: 10.1017/s1355617713001434
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Functioning in Young Children with Type 1 Diabetes

Abstract: Objective To assess cognitive functioning in children with type 1 diabetes (T1D) and examine whether glycemic history influences cognitive function. Research Design and Methods Neuropsychological evaluation of 216 children (healthy controls, n = 72; T1D, n = 144) ages 4-10yrs across five DirecNet sites. Cognitive domains included IQ, Executive Functions, Learning and Memory, and Processing Speed. Behavioral, mood, parental IQ data and T1D glycemic history since diagnosis were collected. Results The cohorts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
86
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 41 publications
1
86
0
7
Order By: Relevance
“…In the neuro-imaging and neuro-cognitive portions of our study, subtle cognitive differences were present in the children with T1D compared with age-matched healthy controls despite relatively short T1D duration (5). Significant differences in brain gray matter volumes (3) and white matter microstructure (12) in widespread brain regions also were observed; these differences were primarily associated with hyperglycemia.…”
Section: Discussionmentioning
confidence: 71%
“…In the neuro-imaging and neuro-cognitive portions of our study, subtle cognitive differences were present in the children with T1D compared with age-matched healthy controls despite relatively short T1D duration (5). Significant differences in brain gray matter volumes (3) and white matter microstructure (12) in widespread brain regions also were observed; these differences were primarily associated with hyperglycemia.…”
Section: Discussionmentioning
confidence: 71%
“…Other current reports in children and adults support the achievement of an HbA 1c <7% (<53 mmol/mol) or <7.5% (<58 mmol/mol) without an increase in SH [11,12,20]. There is an increasing body of evidence that DKA and hyperglycaemia per se, in addition to hypoglycaemia, can have adverse effects on the developing brains of young children [21][22][23]. Thus, it is particularly noteworthy with respect to safety concerns that better HbA 1c outcomes in the DPV registry were associated with a lower frequency of DKA.…”
Section: Discussionmentioning
confidence: 95%
“…Details of the study participants have been previously reported (23–25,34). In brief, children with diabetes ( N = 144) and healthy control subjects without diabetes ( N = 72) between 4 and 10 years of age (mean age at study entry 7.0 years) were recruited for the study, and 210 participants (children with diabetes N = 141, control subjects N = 69) were successfully imaged at both time points.…”
Section: Methodsmentioning
confidence: 99%
“…At study enrollment and after 18 months, all subjects underwent brain imaging and neurocognitive testing (34). Glycemic measures were assessed every 3 months in the group with diabetes.…”
Section: Methodsmentioning
confidence: 99%